Comparative Study of the Antibacterial Activity, Total Phenolic and Total Flavonoid Content of Nine Hypericum Species Grown in Greece - Eleni Kakouri; Dimitra Daferera; Panayiotis Trigas; Despina Charalambous; Maria Pantelidou; Petros A. Tarantilis; Charalabos D. Kanakis (Applied Sciences, 2023)
Hypericum perforatum is an herb whose use dates back centuries. Extracts of the plant are available as over-the-counter treatment options for depression. The genus consists of approximately 500 species, most of which have not yet been studied. Antimicrobial resistance has reached alarming levels, indicating a post-antibiotic era as many of the available treatment options become less effective. For this reason, nine Hypericum species were studied for their antimicrobial activity and their total phenolic and flavonoid content. Extracts were tested against Gram-negative and Gram-positive bacteria. Extracts inhibited the growth of Gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis). The lowest MIC and MBC values were calculated for the extract of H. perforatum against both microorganisms tested, reaching 0.06 mg/mL for S. aureus and 0.13 mg/mL for E. faecalis. Total phenolic content was the highest in the H. perforatum extract (86 ± 12.90 mg GAE/g dry plant material). H. tetrapterum presented the highest flavonoid content, equal to 1.58 ± 0.4 mg RE/g of dry plant material. The Hypericum species studied herein are less common or have not yet been examined compared to H. perforatum; therefore, our study adds new data to the knowledge of the genus Hypericum.